An evaluatıon on the ıntegratıon process of Turkey to the world capıtalıst economıc system after world war II wıthın the framework of uneven and combıned development approach - Özdemir, Çetin (My University, 2016)
Bu tez, Tarihsel Sosyoloji (TS) kapsamında özellikle anaakım Uluslararası İlişkiler (Uİ) teorilerini kritik bir perspektiften ele almaktadır. Anaakım teoriler içsellik ve dışsallık ilişkisini açıklayamamakla, devlet ve Avrupa merkeziyetçi, tarih ve sosyoloji dışı olmakla eleştrilmektedir. Bu bağlamda TS içsel ve uluslararası faktörleri birleştirmeye çalışan bir anlayış güdüp devlet ve Avrupa merkeziyetçi bir yaklaşımın dışına çıkmayı hedeflemekte ve de tarihsel ve sosyolojik bir perspektif takip etmektedir. Özellikle kapitalizm ile devletler sistemi arasındaki ilişki Weberci TS ve Tarihsel Materialist yaklaşımlar tarafından ele alınmaktadır. Bu bağlamda, bu tez Leon Trotsky’nin eşitsiz ve bileşik gelişme (E&BG) yaklaşımını tarihsel sosyolojik öncüller içine yerleştirip uluslararası alanı tarihselleştirme sosyal alanı ise uluslararasılaştırmaya çalışmaktadır. Dolayısıyla bu tez, Türkiye’nin İkinci Dünya Savaşından sonra (1945 ve 1960 arası) kapitalist ekonomik sistem ile bütünleşme sürecinin eşitsiz ve bileşik gelişme dinamiğini güçlü bir biçimde içinde barındırdığını iddia etmektedir. Anahtar Sözcükler: Tarihsel Sosyoloji, anaakım Uİ teorileri, E&BG yaklaşımı, içsellik ve dışsallık sorunu, kapitalizm ve devletler sistemi.

This thesis aims to criticize the mainstream International Relations (IR) theories in the scope of a historical sociological perspective. Especially, the mainstream IR theories cannot explain internal and external issue; they are criticized since they are state and Euro-centric, ahistorical and asociological. In this context, Historical Sociology (HS) aims to pursue a perspective which places IR in social structures and historical processes; in doing so, it combines domestic and international factors; it aims to go beyond a state and Euro centric understanding in line with historical and sociological premises. Particularly, relationship between capitalism and states system is analyzed by both Weberian and historical materialist approaches within historical sociological dynamics. In this context, this thesis places Leon Trotsky’s approach named uneven and combined development (U&CD) in a historical sociological premises within a critical thinking of the traditional IR theories. This thesis raises historicization of international sphere and internationalization of social sphere via U&CD approach under historical materialism. Hence, this thesis expresses that Turkey’s integration process to capitalist economic system after WWII; in other words, between 1945 and 1960 strongly contains process of uneven and combined development. storical Sociology, the mainstream IR theories, U&CD approach, internal and external issue, capitalism and states-system.
Keywords: Avrupa; Dış ilişkiler; Sosyoloji, Tarihsel; Türkiye